SARS-CoV-2 vaccines: A critical perspective through efficacy data and barriers to herd immunity. (April 2021) - Blasi, Francesco; Gramegna, Andrea; Sotgiu, Giovanni; Saderi, Laura; Voza, Antonio; Aliberti, Stefano; Amati, Francesco
Abstract: Non-pharmacological interventions and tracing-testing strategy proved insufficient to reduce SARS-CoV-2 spreading worldwide. Several vaccines with different mechanisms of action are currently under development. This review describes the potential target antigens evaluated for SARS-CoV-2 vaccine in the context of both conventional and next-generation platforms. We reported experimental data from phase-3 trials with a focus on different definitions of efficacy as well as factors affecting real-life effectiveness of SARS-CoV-2 vaccination, including logistical issues associated to vaccine availability, delivery, and immunization strategies. On this background, new variants of SARS-CoV-2 are discussed. We also provided a critical view on vaccination in special populations at higher risk of infection or severe disease as elderly people, pregnant women and immunocompromised patients. A final paragraph addresses safety on the light of the unprecedented reduction of length of the vaccine development process and faster authorization. Highlights: A global vaccination strategy based on efficacious vaccines is among the most relevant unmet needs in COVID-19 management. Vaccine platforms can be conventional and next generation. To date, phase-3 trials are published for 4 vaccines. The definition of vaccine efficacy is challenging and clinical endpoints are heterogeneous. Several factors might affect the effectiveness of a mass vaccination and the herd immunity.